ANALYSIS DISTRIBUTION OF SEA SURFACE TEMPERATURE AND CHLOROPHYLL-a CONCENTRATION IN BELAWAN MEDAN NORTH SUMATRA - Rico Panjaitan; Aras Mulyadi; Musrifin Ghalib (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Sea surface temperature (SST) and chlorophyll-a are important water qualityparameter in the sea, especially the coastal areas. The research was conducted inJanuary - March 2017 in the waters of Belawan, North Sumatera Province with theaim to determine the relationship of sea surface temperature and chlorophyllconcentrations-a.The method used is survey with direct measurements in the watersof Belawan, North Sumatera and using MODIS Aqua satellite image data in March2016 - February 2017. Sea surface temperature MODIS Aqua satellite image datain March 2016 - February 2017 ranged from 29.45 to 31.7oC and chlorophyll-arange of 0.48 to 2.62 mg / l. Field data sea surface temperature ranges from 26-30°Cand chlorophyll-a range of 2.08 to 17.62 mg / l. Interpretation of the data from theMODIS Aqua satellite imagery and field data to explain that the sea surfacetemperature and chlorophyll concentrations-a very weak, r = 0.1791. Data weremapped to show the variability of sea surface temperature and chlorophyll-aconcentrations March 2016 until February 2017.Keywords: Sea Surface Temperature, Chlorophyll-a, Belawan Water